Courtney Egan: Cultivar, June 3 - September 27, 2014 - Frickman, Linny, author; Bookhardt, D. Eric, author; Colorado State University. University Art Museum, publisher (Colorado State University. Libraries, 2014)
New Orleans-based artist, Courtney Egan, received her M.F.A. from the Maryland Institute College of Art in 1993. Since that time she has enjoyed a prolific career as an artist and teacher. Egan’s projection-based sculptural installations have been shown in a number of group and solo exhibitions including NOLA NOW Part II at the Contemporary Arts Center in New Orleans, Louisiana Contemporary at the Ogden Museum of Art, and The World According to New Orleans in Marfa, Texas. The recipient of a number of grants, fellowships and awards, Egan has been honored by the Louisiana Division of the Arts, Louisiana Cultural Economy Foundation, and with a Pollock-Krasner award in association with the Santa Fe Art Institute. She currently is on the faculty of the New Orleans Center for Creative Arts where she teaches in the media arts department.
Exhibition Checklist: Repercussions (Yellow Trumpet), 2010. Single channel HD video installation with sound custom wood speaker cabinet, 11 x 70 x 6 inches; Soft Spots (Japanese Magnolia), 2008. Single channel SD video installation, silent dimensions variable; Sleepwalkers (Night-Blooming Cereus), 2011. Single channel HD video projection, silent approximately 5 x 5 feet; Dreamcatcher (Single Cereus), 2013. Interactive single channel HD video installation, silent webcam, infrared light, computer approximately 4 x 4 feet; Crystal Gazers (Wisteria), 2014. Single channel HD video, ironwork, cast glass and wire 60 x 36 x 11 inches.
Includes the essay, The botanical video art of Courtney Egan, by D. Eric Bookhardt.
The exhibition is part of the Critic and Artist Residency Series, Sponsored by the FUNd at CSU.
Keywords: video art; botanical art; video installations